The pH Sensitivity of Murine Heat Shock Protein 47 (HSP47) Binding to Collagen Is Affected by Mutations in the Breach Histidine Cluster - Abdul-Wahab, Mohd Firdaus (American Society for Biochemistry and Molecular Biology, 2013)
Heat shock protein 47 (HSP47) is a single-substrate molecular chaperone crucial for collagen biosynthesis. Although its function is well established, the molecular mechanisms that govern binding to procollagen peptides and triple helices in the endoplasmic reticulum (followed by controlled release in the Golgi) are unclear. HSP47 binds procollagen at a neutral pH but releases at a pH similar to the pK(a) of the imidazole side chain of histidine residues. It thus seems likely that these residues are involved in this pH-dependent mechanism. Murine HSP47 has 14 histidine residues grouped into three clusters, known as the breach, gate, and shutter. Here, we report the use of histidine mutagenesis to demonstrate the relative contribution of these three clusters to HSP47 structure and the “pH switch.” Many of the tested mutants are silent; however, breach mutants H197A and H198A show binding but no apparent pH switch and are unable to control release. Another breach mutant, H191A, shows perturbed collagen release characteristics, consistent with observed perturbations in pH-driven trans-conformational changes. Thus, His-198, His-197 and His-191 are important (if not central) to HSP47 mechanism of binding/release to collagen. This is consistent with the breach cluster residues being well conserved across the HSP47 family.